2018
DOI: 10.1097/mop.0000000000000595
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypertension in progression of chronic kidney disease in children

Abstract: Hypertension is associated with subclinical cardiovascular disease in children with CKD. Early diagnosis of hypertension by ABPM and identification of subclinical cardiovascular changes provide a window for intervention, which may reverse early cardiovascular disease, thereby delaying dialysis and improving cardiovascular morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…We observed that the body weight loss were reversed in both treated groups, indicating that hiPSCs and RPCs could minimize the impact of CKD on general symptoms, allowing animals to feed regularly, thereby avoiding weight loss, described in CKD [33]. Increased arterial blood pressure levels, another hallmark of CKD, was also partially improved by RPCs and hiPSCs treatment, suggesting that both cell types may have contributed to ameliorating some pathophysiological mechanisms underlying hypertension in CKD [34,35].…”
Section: Discussionmentioning
confidence: 72%
“…We observed that the body weight loss were reversed in both treated groups, indicating that hiPSCs and RPCs could minimize the impact of CKD on general symptoms, allowing animals to feed regularly, thereby avoiding weight loss, described in CKD [33]. Increased arterial blood pressure levels, another hallmark of CKD, was also partially improved by RPCs and hiPSCs treatment, suggesting that both cell types may have contributed to ameliorating some pathophysiological mechanisms underlying hypertension in CKD [34,35].…”
Section: Discussionmentioning
confidence: 72%
“…For example, systolic blood pressure (SBP) as low as 116 mm Hg could be hypertensive in a short 12‐year‐old boy, while 127 mm Hg would not be considered hypertensive in a taller male child of the same age. In turn, failure to recognize hypertensive crises in hospitalized children can result in end‐organ damage or progression of certain chronic diseases 1,11,16,17 . At our institution, we observed that PRN antihypertensive medications were often held without documented explanation, despite ordered administration parameters.…”
Section: Introductionmentioning
confidence: 81%
“…RPCs could minimize the impact of CKD on general symptoms, allowing animals to feed regularly, thereby avoiding weight loss, described in CKD [30]. Increased arterial blood pressure levels, another hallmark of CKD, was also partially improved by RPCs and hiPSCs treatment, suggesting that both cell types may have contributed to ameliorating some pathophysiological mechanisms underlying hypertension in CKD [31,32].…”
Section: Discussionmentioning
confidence: 99%